1991
DOI: 10.1177/002221949102400811
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Literacy Experience and Later Reading Achievement

Abstract: During their children's preschool years, parents were asked about the frequencies of adult reading, parent-child reading, and children's solitary book activities in the home. Parental responses were compared for three groups of children defined according to the parents' reading skills and the children's reading achievement in Grade 2. The results indicated that the 22 preschoolers who became poorer readers had less frequent early literacy-related experiences than the 34 children who became better readers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
135
2
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(155 citation statements)
references
References 11 publications
14
135
2
3
Order By: Relevance
“…Much evidence indicates that children's exposure to literacy-related activities at home is important for children's literacy acquisition (Bus et al, 1995;Dickinson & Tabors, 2001;Scarborough & Dobrich, 1994;Scarborough, Dorich, & Hager, 2001). The relationship between literacy practices at home and children's literacy acquisition is mediated by several important emergent literacy skills -phonological awareness, vocabulary, and letter-name knowledge (Whitehurst et al, 1994;Sénéchal, 2006a;Sénéchal et al, 1998).…”
Section: Background and Contextmentioning
confidence: 99%
“…Much evidence indicates that children's exposure to literacy-related activities at home is important for children's literacy acquisition (Bus et al, 1995;Dickinson & Tabors, 2001;Scarborough & Dobrich, 1994;Scarborough, Dorich, & Hager, 2001). The relationship between literacy practices at home and children's literacy acquisition is mediated by several important emergent literacy skills -phonological awareness, vocabulary, and letter-name knowledge (Whitehurst et al, 1994;Sénéchal, 2006a;Sénéchal et al, 1998).…”
Section: Background and Contextmentioning
confidence: 99%
“…Some studies have revealed small or no relationship between the home literacy environment and literacy outcomes (Bus et al, 1995;Evans, Shaw, & Bell, 2000;Griffin & Morrison, 1997). Other researchers have found a direct relationship, particularly during the preschool years (Britto, 2001;Britto & Brookes-Gunn, 2001;Burgess et al, 2002;Scarborough, Dobrich, & Hager, 1991;Speece et al, 2004;Storch & Whitehurst, 2001). Differences in the measures and methods used in the various studies may explain some of the inconsistencies.…”
Section: Reading Abilitiesmentioning
confidence: 99%
“…A lot of studies investigating this concern show, attitude towards reading and of reading skills success, unsurprisingly are related to each other, and this relationship is both statistically meaningful and positive. Furthermore, it can be seen that a positive attitude towards reading makes a meaningful contribution to high reading success (Rowell 1972(Rowell -1973Szymezuk & Millard 1979;Mason 1980;Roettger, Schofield 1980;Quinn & Jadav 1987;Gottfried 1990;Dobrich & Hager 1991;Wigfield & Guthrie 1997;Greene, Miller, Crowson, Duke & Akey 2004;Scarborough, Wang & Guthrie 2004;Unrau & Schlackman 2006).…”
Section: Introductionmentioning
confidence: 99%